Smart Mini Aquarium Monitoring System - Muhammad Faiq Mughis bin Mohd Jais ,; Ahmad, Nur Azliza (Multidisciplinary Applied Research and Innovation, 2024)
Pet ownership has been increasing steadily over the past 20 years, with freshwater fish now ranking as the third most popular pets after cats and dogs. Maintaining fish aquariums is a challenging task, requiring regular monitoring to ensure the health and well-being of the fish. This report explores the development and effectiveness of an advanced mini aquarium system designed to assist users in maintaining optimal aquarium conditions. The system leverages the ESP32 microcontroller and IoT technology to facilitate real-time communication between devices and users. Key water parameters, including pH and Total Dissolved Solids (TDS), are continuously monitored by sensors. The pH sensor measures the water's acidity and alkalinity, while the TDS sensor detects the total dissolved solids levels, indicating overall water quality. The collected data is transmitted wirelessly to users' smartphones via the Telegram application, allowing for immediate notifications about water conditions. This enables users to promptly address any issues, such as high nitrate levels or suboptimal pH, preventing fish health problems and potential fatalities. The project encompasses the design, implementation, testing, and evaluation of the aquarium system. Detailed analysis demonstrates the system's capability to maintain water quality efficiently, thereby enhancing fish care and simplifying aquarium maintenance. Additionally, the report discusses potential improvements and future developments for the system. By providing real-time data and alerts, the mini aquarium system aims to revolutionize aquarium management, making it more accessible and manageable for pet owners, ensuring the proper care and longevity of their fish.